A food-web assessment model for marine mammals, fish, and fisheries in the Norwegian and Barents Seas - Benjamin Planque; Lucas Bas; Martin Biuw; Marie-Anne Blanchet; Bjarte Bogstad; Elena Eriksen; Hilaire Drouineau; Cecilie Hansen; Bérengère Husson; Erik Askov Mousing; Christian Mullon; Torstein Pedersen; et al. (Progress in Oceanography, 2024)

Multiple stakeholders’ perspectives of marine social ecological systems, a case study on the Barents Sea - Nina Mikkelsen; Benjamin Planque; Per Arneberg; Mette Skern-Mauritzen; Cecilie Hansen; Per Fauchald; Kirstin K. Holsman; Alan C. Haynie; Geir Ottersen (Ocean & Coastal Management, 2023)

Natural mortality estimations for beaked redfish (Sebastes mentella) – A long-lived ovoviviparous species of the Northeast Arctic - Hannes Höffle; Benjamin Planque (Fisheries Research, 2023)

Combined effects of temperature and fishing mortality on the Barents Sea ecosystem stability - Elliot Sivel; Benjamin Planque; Ulf Lindstrøm; Nigel G. Yoccoz (Fisheries Oceanography, 2023)
Temporal variability in abundance and composition of species in marine ecosystems results from a combination of internal processes, external drivers, and stochasticity. One way to explore the temporal variability in an ecosystem is through temporal stability, measured using the inverse of the coefficient of variation for biomass of single species. The effect of temperature and fisheries on the variability of the Barents Sea food web is still poorly understood. To address this question, we simulate the possible dynamics of Barents Sea food web under different temperature and fishery scenarios using a simple food‐web model (Non‐Deterministic Network Dynamic [NDND]). The NDND model, which is based on chance and necessity (CaN), defines the state space of the ecosystem using its structural constraints (necessity) and explores it stochastically (chance). The effects of temperature and fisheries on stability are explored both separately and combined. The simulation results suggest that increasing temperature has a negative effect on species biomass and increasing fisheries triggers compensatory dynamics of fish species. There is a major intra‐scenario variability in temporal stability, while individual scenarios of temperature and fisheries display a weak negative impact and no effect on stability, respectively. However, combined scenarios indicate that fisheries amplify the effects of temperature on stability, while increasing temperature leads to a shift from synergistic to antagonistic effects between these two drivers.

An appraisal of the drivers of Norwegian spring‐spawning herring ( Clupea harengus ) recruitment - Théo Garcia; Benjamin Planque; Per Arneberg; Bjarte Bogstad; Øystein Skagseth; Maik Tiedemann (Fisheries Oceanography, 2021)
Norwegian spring‐spawning herring (NSSH, Clupea harengus ) is a key species in the food‐web and for fisheries in the north‐east Atlantic. NSSH has been the focus of many ecological and fisheries studies over decades and several hypotheses have been put forward to explain variations in its recruitment. We conducted an extensive literature review of the processes that have been hypothesized to control recruitment at age‐2 years. From this review, we constructed a conceptual model to represent how these processes are inter‐connected. We then evaluated several of these hypothesized processes using quantile regression modelling and the most recent available data series as input. Most of the hypotheses were not supported by our analyses. Only two hypotheses were supported: the top‐down control of herring larval stage by Atlantic mackerel ( Scomber scombrus ) and the positive effect of temperature on recruitment. For the latter the interpretation of the results is nevertheless ambiguous when the latest years (1998–2018) of observations are included, as the correlation then changes from positive to negative. Furthermore, when retesting the hypotheses on age‐2 years estimates, we observe a benefitting effect of a consistent strong forcing of the Norwegian Coastal Current and a possible positive effect of the NSSH spawning stock on recruitment. How much these hypotheses can be used to make predictions about future recruitment of herring remains to be tested but based on our results, the relatively short time series available and the dispersion of the observations around the regression models, we can anticipate that such predictions would have limited use for the purpose of fisheries assessment and management.

Suitable habitats of fish species in the Barents Sea - Bérengère Husson; Gregoire Certain; Anatoly Filin; Benjamin Planque (Fisheries Oceanography, 2020)
Many marine species exhibit poleward migrations following climate change. The Barents Sea, a doorstep to the fast‐warming Arctic, is experiencing large scale changes in its environment and its communities. Tracking and anticipating changes for management and conservation purposes at the scale of the ecosystem necessitate quantitative knowledge on individual species distribution drivers. This paper aims at identifying the factors controlling demersal habitats in the Barents Sea, investigating for which species we can predict current and future habitats and inferring those most likely to respond to climate change. We used non‐linear quantile regressions (QGAM) to model the upper quantile of the biomass response of 33 fish species to 10 environmental gradients and revealed three environmental niche typologies. Four main predictors seem to be limiting species habitat: bottom and surface temperature, salinity, and depth. We highlighted three cases of present and future habitat predictability: (a) Habitats of widespread species are not likely to be limited by the existing conditions within the Barents Sea. (b) Habitats limited by a single factor are predictable and could shift if impacted by climate change. If the factor is depth, the habitat may stagnate or shrink if the environment becomes unsuitable. (c) Habitats limited by several factors are also predictable but need to be predicted from QGAM applied on projected environmental maps. These modeled suitable habitats can serve as input to species distribution forecasts and end‐to‐end models, and inform fisheries and conservation management.

A participatory scenario method to explore the future of marine social‐ecological systems - Benjamin Planque; Christian Mullon; Per Arneberg; Arne Eide; Jean‐Marc Fromentin; Johanna Jacomina Heymans; Alf Håkon Hoel; Susa Niiranen; Geir Ottersen; Anne Britt Sandø; Martin Sommerkorn; Olivier Thébaud; et al. (Fish and Fisheries, 2019)
Anticipating future changes in marine social‐ecological systems ( MSES ) several decades into the future is essential in the context of accelerating global change. This is challenging in situations where actors do not share common understandings, practices, or visions about the future. We introduce a dedicated scenario method for the development of MSES scenarios in a participatory context. The objective is to allow different actors to jointly develop scenarios which contain their multiple visions of the future. The method starts from four perspectives: “fisheries management,” “ecosystem,” “ocean climate,” and “global context and governance” for which current status and recent trends are summarized. Contrasted scenarios about possible futures are elaborated for each of the four single perspectives before being integrated into multiple‐perspective scenarios. Selected scenarios are then developed into storylines. Focusing on individual perspectives until near the end allows actors with diverse cultures, interests and horizons to confront their own notions of the future. We illustrate the method with the exploration of the futures of the Barents Sea MSES by 2050. We emphasize the following lessons learned: first, many actors are not familiar with scenario building and attention must be paid to explaining the purpose, methodology, and benefits of scenarios exercises. Second, although the Barents Sea MSES is relatively well understood, uncertainties about its future are significant. Third, it is important to focus on unlikely events. Fourth, all perspectives should be treated equally. Fifth, as MSES are continuously changing, we can only be prepared for future changes if we collectively keep preparing.

Multiple Patterns of Food Web Dynamics Revealed by a Minimal Non-deterministic Model - Ulf Lindstrøm; Benjamin Planque; Sam Subbey (Ecosystems, 2017)

Who eats whom in the Barents Sea: a food web topology from plankton to whales - Benjamin Planque; Raul Primicerio; Kathrine Michalsen; Michaela Aschan; Grégoire Certain; Padmini Dalpadado; Harald Gjøsæater; Cecilie Hansen; Edda Johannesen; Lis Lindal Jørgensen; Ina Kolsum; Susanne Kortsch; et al. (Ecology, 2014)
A food web is an ecological network and its topological description consists of the list of nodes, i.e., trophospecies, the list of links, i.e., trophic interactions, and the direction of interactions (who is the prey and who is the predator). Food web topologies are widely used in ecology to describe structural properties of communities or ecosystems. The selection of trophospecies and trophic interactions can be realized in different manners so that many different food webs may be constructed for the same community. In the Barents Sea, many simple food webs have been constructed. We present a comprehensive food web topology for the Barents Sea ecosystem, from plankton to marine mammals. The protocol used to compile the data set includes rules for the selection of taxa and for the selection and documentation of the trophic links. The resulting topology, which includes 244 taxa and 1589 trophic links, can serve as a basis for topological analyses, comparison with other marine ecosystems, or as a basis to build simulation models of the Barents Sea ecosystem. The data set consists of three related tables: (1) the list of taxa, (2) the list of pairwise interactions, and (3) the list of bibliographical references.

Choices of abundance currency, community definition and diversity metric control the predictive power of macroecological models of biodiversity - Grégoire Certain; Carsten F. Dormann; Benjamin Planque (Global Ecology and Biogeography, 2014)
Aim This study focuses on the influence of methodological choices on the predictive performance of macroecological models ( MEM s), i.e. statistical models designed to predict patterns of biodiversity using environmental predictors. We emphasize the influence of three methodological choices: (1) the choice of the currency in which the abundance of each species is measured, i.e. numbers of individuals or biomass; (2) the rules used to define the species assemblage under focus, i.e. broad communities or refined ecological guilds; and (3) the influence of rare over common species in the biodiversity measure. Location The effects of these choices are investigated using an exhaustive dataset on the fish fauna of the continental shelf of the B arents S ea. Methods We conducted an analysis of 220 models resulting from all possible combinations of the three methodological choices. For each, we evaluated the predictive performance through an iterative cross‐validation process. Results All methodological choices we investigated strongly affected the predictive performance of MEM s. High predictive performances were obtained when using biomass instead of numbers of individuals, when focusing on narrow ecological guilds composed of species sharing the same ecological traits and when using diversity measures that give high weight to rare species. Main conclusions We recommend that future projections of biodiversity pay more attention to abundance currency, ecological homogeneity of focal species assemblages and the diversity metric used, and systematically investigate these methodological choices prior to producing biodiversity forecasts. Splitting a whole set of species into ecological guilds appears to be a promising practice, leading to a selected set of MEMs with high predictive performances and more detailed forecasts on the fate of diversity.

Potential movement of fish and shellfish stocks from the sub‐ A rctic to the A rctic O cean - Anne Babcock Hollowed; Benjamin Planque; Harald Loeng (Fisheries Oceanography, 2013)
An assessment of the potential for 17 fish or shellfish stocks or stock groups to move from the sub‐ A rctic areas into the A rctic O cean was conducted. A panel of 34 experts was convened to assess the impact of climate change on the potential movement of the 17 stocks or stock groups. The panel considered the exposure of species to climate change, the sensitivity of species to these changes and the adaptive capacity of each stock or stock group. Based on expert opinions, the potential for expansion or movement into the A rctic was qualitatively ranked (low potential, potential, high potential). It is projected that the A rctic O cean will become ice‐free during the summer season, and when this happens new areas will open up for plankton production, which may lead to new feeding areas for fish stocks. Five stocks had a low potential to move to, or expand in, the high A rctic. Six species are considered as potential candidate species to move to, or expand in, the high A rctic. Six stocks had a high potential of establishing viable resident populations in the region. These six stocks exhibit life history characteristics that allow them to survive challenging environmental conditions that will continue to prevail in the north. This study suggests that several life history factors should be considered when assessing the potentiality of a species moving in response to changing climate conditions.

Understanding what controls the spawning distribution of North Sea whiting ( Merlangius merlangus ) using a multi‐model approach - CHRISTOPHE LOOTS; SANDRINE VAZ; BENJAMIN PLANQUE; PHILIPPE KOUBBI (Fisheries Oceanography, 2011)
The processes that control the spatial distribution of North Sea whiting ( Merlangius merlangus ) spawning adults are investigated using a statistical multi‐model approach. Models of external and internal controls on the population, such as environmental conditions, spatial constraints, present or past spatial distribution, and demographic state of the population, are evaluated, compared and ranked to select those that are the best able to predict the observed distribution of spawning adults. Model selection is greatly influenced by the selection method, either based on data fitting or prediction, as well as by the threshold value used to stop the selection. Model selection based on prediction tends to select simpler models than selection based on data fitting. The hypotheses underlying the selected models are inferred to play a significant role in controlling North Sea whiting spatial distribution. The multi‐model inference approach developed in this study enables comparison of several theoretical concepts and hypotheses and the results provide important clues on the processes involved in the control of the spatial distribution of whiting. We conclude that whiting has a high spatial fidelity to spawning site which can be linked to either geographical attachment or year‐to‐year persistence of the spatial distribution of the population. Environmental factors – temperature and salinity – appear to influence the geographical extent of spawning whiting distribution, whereas local abundance levels are primarily controlled by internal factors, i.e., population size and spatial segregation between ages.

Understanding what controls the spatial distribution of fish populations using a multi‐model approach - BENJAMIN PLANQUE; CHRISTOPHE LOOTS; PIERRE PETITGAS; ULF LINDSTRøM; SANDRINE VAZ (Fisheries Oceanography, 2011)
Understanding and predicting the distribution of organisms in heterogeneous environments lies at the heart of ecology. The spatial distribution of fish populations observed in the wild results from the complex interactions of multiple controls both external or internal to the fish populations. Whilst species distribution models (SDMs) have been mostly concerned with static description of species distribution as a function of environmental constraints, models of animal movements (MAMs) have focussed on the dynamic nature of spatial distribution of groups of individuals under a number of constraints external and internal to the population. Besides SDMs and MAMs, modelling the spatial distribution of fish populations can be achieved by models that are fundamentally static (like SDMs) but can also incorporate many hypotheses on the control of fish spatial distribution (like MAMs). The hypotheses underlying these models need to make sense at the population level ‐ rather than at the individual or species level –we term these ‘population distribution models’ (PDMs). PDMs are statistical models that rely on several hypotheses, which include: (i) control through geographical attachment, (ii) environmental conditions, (iii) density‐dependent habitat selection, (iv) spatial dependency, (v) population demographic structure, (vi) species interactions and (vii) population memory. We review the basis behind each of these conceptual models and we examine corresponding numerical applications. We argue that the conceptual models are complementary rather than competing, that existing numerical applications are still rarely compared and combined, and that PDMs can offer a statistical framework to achieve this. We recommend that the numerical models associated with different hypotheses be constructed within such a common general framework. This will permit evaluation, comparison and combination of the multiple hypotheses on fish spatial distribution. It will ultimately lead to a more comprehensive understanding of the factors controlling the spatial distribution of fish populations and to more accurate predictions in which model uncertainty is accounted for.

Modelling potential spawning habitat of sardine ( Sardina pilchardus ) and anchovy ( Engraulis encrasicolus ) in the Bay of Biscay - BENJAMIN PLANQUE; EDWIGE BELLIER; PASCAL LAZURE (Fisheries Oceanography, 2007)
Large amplitude variations in recruitment of small pelagic fish result from interactions between a fluctuating environment and population dynamics processes such as spawning. The spatial extent and location of spawning, which is critical to the fate of eggs and larvae, can vary strongly from year to year, as a result of changing population structure and environmental conditions. Spawning habitat can be divided into ‘potential spawning habitat’, defined as habitat where the hydrographic conditions are suitable for spawning, ‘realized spawning habitat’, defined as habitat where spawning actually occurs, and ‘successful spawning habitat’, defined as habitat from where successful recruitment has resulted. Using biological data collected during the period 2000–2004, as well as hydrographic data, we investigate the role of environmental parameters in controlling the potential spawning habitat of anchovy and sardine in the Bay of Biscay. Anchovy potential spawning habitat appears to be primarily related to bottom temperature followed by surface temperature and mixed‐layer depth, whilst surface and bottom salinity appear to play a lesser role. The possible influence of hydrographic factors on the spawning habitat of sardine seems less clear than for anchovy. Modelled relationships between anchovy and sardine spawning are used to predict potential spawning habitat from hydrodynamical simulations. The results show that the seasonal patterns in spawning are well reproduced by the model, indicating that hydrographic changes may explain a large fraction of spawning spatial dynamics. Such models may prove useful in the context of forecasting potential impacts of future environmental changes on sardine and anchovy reproductive strategy in the north‐east Atlantic.

Historical fluctuations in spawning location of anchovy ( Engraulis encrasicolus ) and sardine ( Sardina pilchardus ) in the Bay of Biscay during 1967–73 and 2000–2004 - EDWIGE BELLIER; BENJAMIN PLANQUE; PIERRE PETITGAS (Fisheries Oceanography, 2007)
The spatial extent of small pelagic fish spawning habitat is influenced by environmental factors and by the state of the adult population. In return, the configuration of spawning habitat affects recruitment and therefore the future structure of the adult population. Interannual changes in spatial patterns of spawning reflect variations in adult population structures and their environment. The present study describes the historical changes in the spatial distribution of spawning of anchovy ( Engraulis encrasicolus ) and sardine ( Sardina pilchardus ) in the Bay of Biscay during two periods: 1967–72 and 2000–2004. Using data from egg surveys conducted in spring, the spatial distributions of anchovy and sardine eggs are characterized by means of geostatistics. For each survey, a map of probability of egg presence is constructed. The maps are then compared to define (1) recurrent spawning areas, (2) occasional spawning areas and (3) unfavourable spawning areas during each period. Sardine spawning habitat is generally fragmented and appears spatially limited by the presence of cold bottom water. It is confined to coastal or shelf break refuge areas in years of restricted spawning extent. For anchovy, recurrent spawning sites are found in Gironde and Adour estuaries whilst spawning can extend further offshore in years of more intense spawning. For both species, the mean pattern of spawning has changed between 1967–72 and 2000–2004. Noticeably, the spatial distribution of anchovy eggs in spring has expanded northward. This trend possibly results from changes in environmental conditions during the last four decades.

Ecological effects of the North Atlantic Oscillation - Geir Ottersen; Benjamin Planque; Andrea Belgrano; Eric Post; Philip C. Reid; Nils C. Stenseth (Oecologia, 2001)

Is observed variability in the long‐term results of the Continuous Plankton Recorder survey a response to climate change? - PHILIP C. REID; BENJAMIN PLANQUE; MARTIN EDWARDS (Fisheries Oceanography, 1998)
In the more than 50 years that the Continuous Plankton Recorder (CPR) survey has operated on a regular monthly basis in the north‐east Atlantic and North Sea, large changes have been witnessed in the planktonic ecosystem. These changes have taken the form of long‐term trends in abundance for certain species or stepwise changes for others, and in many cases are correlated with a mode of climatic variability in the North Atlantic, either: (1) the North Atlantic Oscillation (NAO), a basin‐scale atmospheric alteration of the pressure field between the Azores high pressure cell and the Icelandic Low; or (2) the Gulf Stream Index (GSI), which measures the latitudinal position of the north wall of the Gulf Stream. Recent work has shown that the changes in the GSI are coupled with the NAO and Pacific Southern Oscillation with a 2 year lag. The plankton variability is also possibly linked to changes observed in the distribution and flux of water masses in the surface, intermediate and deep waters of the North Atlantic. For example, in the last two decades, the extent and location of the formation of North Atlantic Deep Water, Labrador Sea Intermediate Water and Norwegian Sea intermediate and upper‐layer water has altered considerably. This paper discusses the extent to which observed changes in plankton abundance and distribution may be linked to this basin‐scale variability in hydrodynamics. The results are also placed within the context of global climate warming and the possible effects of the observed melting of Arctic permafrost and sea ice on the subpolar North Atlantic.